THU0226 Evaluation of Serum 14-3-3Eta Levels in A Japanese RA Cohort Treated with Tocilizumab. (10th June 2014) - Sagawa, A.; Kaneda, M.; Gui, Y.; Marotta, A.; Arai, J.
Abstract : Background: Serum 14-3-3η is a novel protein biomarker for rheumatoid arthritis (RA) and is available for clinical use in the United States, Europe, and Canada. It precedes the onset of RA and its presence is associated with the development of RA. Objectives: In this study, we investigated whether serum 14-3-3η is useful as a marker for RA disease activity and a predictive factor for therapeutic efficacy of tocilizumab. Methods: Serum 14-3-3η protein levels were measured in 41 patients (median age 54 yrs, range 20–78 yrs) with RA before and 12-weeks after treatment with tocilizumab (8 mg/kg iv every 4 weeks), using the Augurex 14-3-3η ELISA kit (positive ≥0.19 ng/ml). Median DAS28-ESR and CDAI of the RA cohort before treatment were 5.1 (range 2.1–7.5) and 22.7 (range 10.4–60.8), respectively. 31 of 41 patients were ACPA positive, 37 were MMP3 positive and 1 was negative for both markers. Mann-Whitney U-tests and Fisher's exact tests were performed for comparison between treatment groups. A regression analysis was performed to determine if serum 14-3-3η levels was an independent predictor of a Good EULAR response and remission, DAS <2.6. Results: At pre-treatment, 28 (68%) of 41 patients were 14-3-3η positive and the 14-3-3η positive group tended to have higher baseline DAS28-ESR (4.5 vs 5.3, p =0.055) and CDAI (20.0 vs 25.4, p =0.046). The paired t-test revealed that 14-3-3η levels were significantly lower post-treatment with tocilizumab (4.7 vs 3.7, p =0.028). Patients with a post-treatment decrease in 14-3-3η had a significantly greater change in MMP3 levels compared to the group with no decrease (54.8 vs 8.0, p =0.027). The change in ACPA, DAS28-ESR and CDAI did not differ between the two 14-3-3η groups. According to the EULAR response criteria, the group of good responders ( n =17) had significantly lower pre-treatment 14-3-3η levels compared to the group of moderate and no responders ( n =24), 0.37 vs 1.76 ng/ml, p =0.0252. Similarly, the pre-treatment 14-3-3η levels were significantly lower in the group of patients that achieved remission ( n =13) by DAS28-ESR (<2.6). Neither ACPA nor MMP-3 levels was different between these responder groups. Fisher's exact testing revealed an association ( p =0.045) between DAS remission and 14-3-3h negativity delivering an odds ratio (OR) of 3.4 (95% CI: 0.9–13.3). No association between 14-3-3h and a good EULAR response was observed. Regression analysis controlling for baseline DAS28-ESR revealed that 14-3-3h titres were an independent predictor of remission yielding a likelihood ratio (LR) of 7.8, p =0.0052. Conclusions: Serum 14-3-3η protein is a biomarker that may predict efficacy of tocilizumab treatment for RA. Further study is required to establish the usefulness of 14-3-3η in terms of treatment with other biologics and/or long-term administration of tocilizumab. Disclosure of Interest: : None declared DOI: 10.1136/annrheumdis-2014-eular.4942